Effects of industrial and investigator disturbance on Arctic‐nesting geese. Issue 8 (17th July 2017) - Meixell, Brandt W.; Flint, Paul L.
ABSTRACT: Oil and gas development on the Arctic Coastal Plain (ACP) of Alaska, USA may have effects on Arctic‐nesting birds. To estimate effects of industrial activity and investigator disturbance on avian productivity, we monitored nests of greater white‐fronted geese ( Anser albifrons ) with digital cameras and periodic nest visits during 2013–2014 at 2 sites on the ACP. A disturbed site was adjacent to human‐made infrastructure and industrial clean‐up activities initiated at the onset of the study and a control site was >2 km from sources of industrial disturbance. We assessed variation in estimates of incubation constancy, nest survival, and predator behavior relative to site, year, and distance from industrial activity using nest photographs obtained at 1‐minute intervals. We compared analysis of hourly nest survival informed by intensive monitoring with cameras to analysis of daily nest survival informed by traditional nest visit data obtained at intervals of 5–7 days to assess how method and time scale of sampling affect ecological inference. Geese in both sites exhibited high levels of nest attendance and initiated incubation breaks less than once per day. Observer‐caused incubation breaks associated with nest visits ( x ¯  = 37.8 min) were longer than other types of incubation breaks ( x ¯  = 8.7 min), demonstrating a differential response by nesting geese to direct human encroachment versus indirect vehicular and aircraft traffic. During both years, geese were absent from nests more frequently in the disturbed ( x ¯  = 0.9 breaks/day) than control ( x ¯  = 0.6 breaks/day) site, and this break frequency was slightly higher for nests closer to industrial activity. In the year with high rates of depredation, nest survival was positively related to distance from industrial activity and abandoned infrastructure, consistent with predictions of industry‐caused effects. This relationship, however, was not evident in the year with reduced predation pressure, likely because of annual variation in arctic fox ( Vulpes lagopus ) behavior. Analysis of nest survival probability informed by camera data allowed for detection of detailed patterns of variation that were not supported when using only visit data for the same nests. Observer visits were responsible for reductions of 7–35% in nest survival probability, highlighting the importance of minimizing, and controlling for, observer effects in studies of avian productivity. Indirect vehicular and aircraft disturbance posed less risk to nest survival than direct encroachment by observers at nest sites. Therefore, effects of industrial activities on avian productivity in the Arctic can be minimized through practices that limit direct encounters with nests. Published 2017. This article is a U.S.Government work and is in the public domain in the USA. Abstract : Industrial disturbance, characterized by indirect vehicular and aircraft traffic, had minor negative impacts on incubation constancy of white‐fronted geese. In contrast, nest visits by researchers caused prolonged incubation recesses and increased the probability of egg depredation. Impacts of industrial and research activity in the Arctic can be minimized through practices that limit direct encounters with nests.